Landscape-Scale Effects of Forest Degradation on Insectivorous Birds and Invertebrates in Austral Temperate Forests - Vergara-Egert, P; Llanos-Ascencio, J; Fierro-Tapia, C; Alaniz-Baeza, A (Springer Science and Business Media B.V., 2021)
Context: Insectivorous birds are sensitive to forest disturbances that may limit the availability of food consisting mainly of invertebrates. However, birds and invertebrates may be differently affected by forest disturbances while invertebrates may interact with disturbances. Objectives: We aim to determine: (i) the effects of forest degradation on invertebrates and insectivorous birds; (ii) the effect of the availability of invertebrates as a food source on birds; (iii) interactions between food availability and forest degradation. Methods: We selected 34 1-km radius landscape units, where the abundance of birds and invertebrates was sampled in the canopy and understory. Bird density as well as the abundance and richness of invertebrates were considered as dependent variables and analysed using Generalized Linear Mixed Model and Structural Equation Models. Remote-sensing indices of forest degradation were included as predictors. Results: Eight indices of forest degradation affected canopy and understory invertebrates differently. Unlike invertebrates, bird abundance was affected by a smaller number of degradation indices, forest amounts as well as the cover of understory and canopy. Only two forest degradation indices had a comparable effect on bird abundance and invertebrates. We found causal relationships between understory invertebrates and the abundance of understory birds (all species and the small-sized ones), but also invertebrate abundance × forest cover interactions affected the abundance of a bird species. Conclusions: Our results indicate that birds and invertebrates respond differently to forest degradation, but also provide evidence for bottom-up control by forest degradation and suggest food limitation varies with forest amounts. © 2020, Springer Nature B.V.
Keywords: Insectivorous birds; Invertebrates; Bottom-up control; Temperate forests